Antimicrobial Effect of Calcium Hydroxide Combined with Electrolyzed Superoxidized Solution at Neutral pH on Enterococcus faecalis Growth - Héctor Armando Jimenez-Gonzalez (Hindawi Limited, 2021)
Objective. To evaluate the effect of the combination of calcium hydroxide (Ca(OH)2) and a novel electrolyzed superoxidized solution at neutral pH, known as OxOral® on Enterococcus faecalis growth in root canals. Methods. Sixty human teeth were used, from which root canals were infected and randomly divided into the following treatment groups: saline solution, saline solution plus Ca(OH)2, OxOral®, and OxOral® plus Ca(OH)2. Results. A permanent reduction in bacterial growth was observed at days 1, 6, 12, and 18 after OxOral® plus Ca(OH)2 treatment from 4.4±0.074 log10 CFU/mL to 0.0±0.001 log10 CFU/mL. In addition, alkaline conditions maintenance was observed from application time (pH=12.2±0.033) to 18 d posttreatment (pH=12.6±0.083). Conclusion. The combination of OxOral® and Ca(OH)2 provides an alkaline pH and inhibits E. faecalis growth into the root canals. Our study opens the possibility for further research on the use of OxOral® in endodontic therapy.